Autistic Student Teacher’s Pedagogical Competence in the English Language Teaching - Tiyas Saputri; Syafiul Anam; Ahmad Munir (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to investigate the autistic student teacher’s pedagogical competence in the English Language Teaching (ELT) practicum based on eight teaching skills, the difficulties he faced, and the strategies to support the autistic student teacher applying his pedagogical competence in the ELT. Method: The method used was a descriptive qualitative with a case study approach. Data collection techniques used in this study were observation, interview, and video recording. Data analysis techniques were dividing observational field notes, doing data reduction, describing and identifying the activity of the autistic student teacher applying his pedagogical competence in the ELT practicums based on the eight teaching skills, and making a conclusion. Results: The results of the study indicated that the autistic student teacher’s pedagogical competence in English Language Teaching based on the eight teaching skills in the eighth grade of inclusion class at 39 Junior High School Surabaya was good, although it was not successfully completed. It was obtained that he only did five to eight teaching skills. He had only skills in questioning, doing reinforcement, doing variation, explaining, opening and closing the class. Three teaching skills had yet to be fully mastered by him. The difficulties faced by him were classroom management, small group discussion and organizing small group discussion and individual work with the students. Novelty: This study focused on the autistic student teacher’s pedagogical competence in the English Language Teaching (ELT) practicum based on eight teaching skills. No study investigates the pedagogical competence of autistic student teacher in ELT, mostly the previous researches investigated the pedagogical competence of the student teacher with a normal condition.